2021
DOI: 10.1002/ecs2.3651
|View full text |Cite
|
Sign up to set email alerts
|

Site‐specific impacts of a major hurricane on alpha and beta diversity in tropical forest seedling communities

Abstract: Site-specific impacts of a major hurricane on alpha and beta diversity in tropical forest seedling communities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 78 publications
(190 reference statements)
0
4
0
Order By: Relevance
“…That is, richness differences were particularly high between environmentally heterogeneous localities within elevations. Environmental heterogeneity has been described as very important for species richness across many taxa and at different spatial scales (Stein et al 2014, Worthy et al 2021). Additionally, topography has been reported as a prominent driver of the high local diversity of trees in the study area (Homeier et al 2010).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…That is, richness differences were particularly high between environmentally heterogeneous localities within elevations. Environmental heterogeneity has been described as very important for species richness across many taxa and at different spatial scales (Stein et al 2014, Worthy et al 2021). Additionally, topography has been reported as a prominent driver of the high local diversity of trees in the study area (Homeier et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Pinto‐Ledezma et al (2018) showed that high turnover of plant species occurred mainly in stable climates with higher species richness, while richness differences contributed to beta‐diversity of plant communities in less diverse biomes with high environmental variability. So far, most studies investigated the role of environmental filtering to explain regional patterns of beta‐diversity (Condit et al 2002, Swenson et al 2011, Worthy et al 2021). However, cross‐scale comparisons of beta‐diversity are needed to disentangle the effects of environmental factors and biotic interactions on local and regional diversity in plant communities (Kraft et al 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effects of tropical cyclones as environmental drivers for species assemblages in various ecosystems are well established (Lin et al., 2020; Morrison & Spiller, 2008). Depending on the ecological context, tropical cyclones can have homogenizing or non‐homogenizing effects on community composition (Worthy et al., 2021). Homogenizing effects can arise due to selective, deterministic mortality/survival (McCoid, 1996), a reduction in environmental heterogeneity (Comita et al., 2010), and synchronized succession trajectories following the disturbance event (Xi et al., 2019).…”
Section: Introductionmentioning
confidence: 99%